Density‐dependent modulation of copepod body size and temperature–size responses in a shelf sea. Issue 11 (17th September 2021) - Corona, Stefano; Hirst, Andrew; Atkinson, David; Atkinson, Angus
Abstract: Body size is a fundamental trait in ecology, and body size reduction with increasing temperature has been termed the third universal response to climate warming. Although effects of temperature and food on phenotypic plasticity of zooplankton adult body size have been investigated, density‐dependent effects have been neglected. We measured seasonal changes in the prosome length of 7098 adult females of 7 dominant copepod species in 13 yr spanning a 27‐yr period of warming at the L4 time series off Plymouth, UK. The seasonal temperature–size (T–S) response varied greatly among species, from reductions of 2.93% of carbon mass °C −1 for Paracalanus parvus to 10.15% of carbon mass °C −1 for Temora longicornis . Evidence for a long‐term T–S response was detected in at least two species, supporting the hypothesis that climatic warming leads to smaller adult sizes. April was a crucial month for determining the strength of the T–S response. During this month, body size related negatively to total zooplankton abundance. We suggest that the mechanism for this density dependence is via competition for food and/or intraguild predation, since spring was also the period when the ratio of food biomass to zooplankton biomass was at its lowest. Our study is among the first in situ demonstrations of density‐dependent effects on the body size of marine zooplankton and shows the need to consider the effect of top‐down as well as bottom‐up factors on body size in a warming climate.